AB0263 Agreement between Das28, Acr/eular, Sdai, Cdai and Ultrasound Remission in Patients with Rheumatoid Arthritis Receiving Biological Treatment in Routine Care. (15th July 2016) - Brahe, C.H.; Terslev, L.; Krabbe, S.; Østergaard, M.; Røgind, H.; Jensen, H.S.; Hansen, A.; Nørregaard, J.; Jacobsen, S.; Ellegaard, K.; Fana, V.; Juul, L.; et al.
Abstract : Background: Different remission criteria are available for patients with rheumatoid arthritis (RA). None of the criteria includes imaging remission, even though studies have shown that many RA patients in sustained clinical remission have synovitis detectable by ultrasound (US), i.e. grey scale synovial hypertrophy and/or Doppler signal in the synovium. Objectives: We aimed to investigate the agreement between different clinical remission criteria and remission defined by US in patients with RA receiving biological therapy in routine care. Methods: A total of 117 RA patients in sustained remission (i.e. DAS28 ≤2.6 for ≥1 year and no radiographic progression the last year) on biological therapy were recruited. All patients underwent US of 24 joints for grading of grey scale (GS) synovial hypertrophy (0–3) and synovial Colour Doppler activity (CD) (0–3). Imaging remission was defined in two ways: either GS=0 and CD=0 in all 24 joints, or GS≤1 and CD=0 in all 24 joints. Results: Baseline characteristics are shown in table 1 . At baseline patients received the following disease-modifying antirheumatic drugs (DMARDs): methotrexate (MTX; 72%), sulphasalazine (3%), azathioprine (2%), leflunomide (2%), no DMARDs (21%) and the following treatment with biological therapy: abatacept (2%), adalimumab (28%), certolizumab (3%), etanercept (28%), golimumab(3%), infliximab (27%), tocilizumab (9%). For patients fulfilling DAS28 remission criteria, US defined remission was present in 9% (GS=0 and CD=0 in all 24 joints, termed "very strict" US remission) or 29% (GS ≤1 per joint and CD=0 in all 24 joints, termed "strict" US remission) and 24% had CD>1 in at least 1 joint (table 1 ). For patients fulfilling other criteria for clinical remission (CDAI, SDAI and ACR/EULAR remission), patients were in very strict US remission in 12%, 12% and 10%, respectively and in strict US remission in 28%, 29% and 20%, respectively. CD activity >1 in at least 1 joint was present in 22%, 25% and 22% of patients, respectively. The anatomical distribution of the GS synovial hypertrophy was 31% in metacarpophalangeal joints, 27% in metatarsophalangeal joints, 19% in wrists, 10% in knees, 7% in elbows and 6% in ankles. Thus, 33% of the total GS synovial hypertrophy was observed in the feet, which are not included in the DAS28 remission criteria. There were no significant differences in US findings (GS or CD) between patients in remission vs patients not in remission, no matter which clinical remission criteria were used. Conclusions: Subclinical synovitis was frequently detected by US in RA patients treated with biological drugs in routine care showing poor agreement between the clinical remission criteria and US remission. Further studies are needed to evaluate the benefit of US remission as a goal for treat to target strategies on patient-reported outcomes and radiographic progression. Disclosure of Interest: C. H. Brahe: None declared, L. Terslev: None declared, S. Krabbe: None declared, M. Østergaard Grant/research support from: Abbvie, BMS, Boehringer-Ingelheim, Eli Lilly, Janssen, Merck, Pfizer, Roche, UCB, Celgene, Sanofi, Regeneron, Novartis, T.Jensen, H. Røgind: None declared, H. Jensen: None declared, A. Hansen: None declared, J. Nørregaard: None declared, S. Jacobsen: None declared, K. Ellegaard: None declared, V. Fana: None declared, L. Juul: None declared, T. Huynh: None declared, D. Jensen: None declared, N. Manilo: None declared, K. Asmussen Speakers bureau: Novartis, Abbvie, Pfizer, Berlin Chemie, MSD, UCB, P. Frandsen: None declared, S. Pedersen: None declared, N. Krogh: None declared, M. Hetland: None declared